SEMIOTIC ANALYSIS OF THE POEM A CONVERSATION WITH MY MOTHER ABOUT THE BLOODSTAINS ON MY SHIRT BY DARIUS SIMPSON - Lase, Rosmawati; safitri, Mayshia; Fitriyah, Fitriyah (Universitas Islam Sumatera Utara (UISU), 2025)
Leech’s semantic theory plays a crucial role in analyzing meaning in a poem, as it highlights the multiple layers of interpretation embedded in poetic language. The aim of this study is to analyse the types of meaning in the poem “A Conversation with My Mother about the Bloodstains on My Shirt” by Darius Simpson. This study employs Leech's semantic theory as the primary theoretical framework for interpreting the semiotic meanings present in the poem's text. The research method used in this study is a qualitative descriptive approach, using content analysis of Leech’s semantic categories. The findings reveal six distinct types of meaning in the poem. They are conceptual meaning (16 %), connotative meaning (27 %), affective meaning (18%), thematic meaning (16 %), social meaning (18%), and reflected meaning (4%). The dominant meaning is connotative, emphasizing the emotional burden and sociopolitical critique of the poet. While the least is reflected meaning, because the poem prioritizes clarity, emotional resonance, and sociopolitical truth, rather than wordplay or associative ambiguity. Therefore, this study provides a comprehensive lens for interpreting how poets use linguistic creativity to communicate meaning in subtle, layered, and aesthetic ways.